Restorative Justice Approach to The Settlement of Banking Crime Cases - Hijriani Hijriani; La Niasa; Ayu Lestari Dewi; Muhammad Yusuf (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2023)
Banking crimes can now occur in a variety of new forms, which not only harm people or the wider community, but can also cause losses to the state and even the global economy. Settlement of corporate crimes, particularly banking crimes, still leads to legal accountability through diverse statutory instruments, and the imposition of sanctions tends to be oriented toward the perpetrator's criminal responsibility rather than representing the victim's interests. The purpose of this study is to examine non-litigation dispute resolution in the context of corporate banking crimes, as well as whether the concept of restorative justice can be used as an alternative to sanctions in the resolution of corporate banking crimes. The normative legal research method is used, with analytical, comparative, and statutory approaches. The study's findings indicate that the disputing parties can use the out-of-court settlement mechanism to reach an agreement. The use of this mechanism must be established through an injunction settlement institution, as it is known in the legal systems of the United States and the United Kingdom. The court may order a delay in examining the case at the request of one of the litigants if the applicant can demonstrate that there is no clear legal means. The concept of restorative justice opens the door to alternative solutions to corporate banking crimes, such as the deferred prosecution agreement policy.